The Days Between : Blessings, Poems, and Directions of the Heart for the Jewish High Holiday Season - Falk, Marcia (Book collections on Project MUSE., 2014)
In 5 parts. Part 1 offers parallel English & Hebrew blessings and prayers for home, synagoge, and other settings. Part 2 offers a psalm (poem) and a direction (essay) for each day between Rosh Hashanah and Yom Kippur. Part 3 is parallel English & Hebrew blessings and prayers for Yom Kippur. Part 4 is a newly constructed non-hierarchical liturgy (Entering the Gates), and Part 5 is an essay about the newly constructed liturgy of part 4.